Predator-prey interactions, age structures and delay equations - Mohr, Marcel; Barbarossa, Maria Vittoria; Kuttler, Christina (Mathematical modelling of natural phenomena, 2014)
The Mathematical Modelling of Natural Phenomena (MMNP) is an international research journal, which publishes top-level original and review papers, short communications and proceedings on mathematical modelling in biology, medicine, chemistry, physics, and other areas.